2018
DOI: 10.1111/eva.12644
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted DNA metabarcoding: Validation of a noninvasive, next‐generation approach to studying bat populations

Abstract: As multiple species of bats are currently experiencing dramatic declines in populations due to white‐nose syndrome (WNS) and other factors, conservation managers have an urgent need for data on the ecology and overall status of populations of once‐common bat species. Standard approaches to obtain data on bat populations often involve capture and handling, requiring extensive expertise and unavoidably resulting in stress to the bats. New methods to rapidly obtain critical data are needed that minimize both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 70 publications
0
35
0
Order By: Relevance
“…The DNA metabarcoding of bat faecal pellets can offer valuable insights into the dietary preferences of bats and their potential role as pest suppressors (Bohmann et al, 2014;Swift et al, 2018). Recent diet analyses of multiple bat species have detected a wide range of arthropods in bat populations (Galan et al, 2017) including several economically important pest species (Taylor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA metabarcoding of bat faecal pellets can offer valuable insights into the dietary preferences of bats and their potential role as pest suppressors (Bohmann et al, 2014;Swift et al, 2018). Recent diet analyses of multiple bat species have detected a wide range of arthropods in bat populations (Galan et al, 2017) including several economically important pest species (Taylor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that both E. fuscus and M. lucifugus consumed insect pest species, although these data cannot be used to quantify the abundance of these species in the diet or the overall effect on the population of these insect pests (Swift et al. ). Also, of the insect pests consumed by M. lucifugus , there was an increase in the number of these consumed by E. fuscus in response to the decline of M. lucifugus .…”
Section: Discussionmentioning
confidence: 90%
“…), but DNA processing methods are still not suitable for directly quantifying the abundance of prey items in the bat diet (Swift et al. ). Therefore, future studies should focus on ways to calculate the volume of each prey item in a sample, which can then be extrapolated to determine the impact of bats feeding on insects.…”
Section: Discussionmentioning
confidence: 99%
“…Swift et al. () utilized MIS methods and multifaceted DNA metabarcoding (MDM) to obtain six different data classes of genetic information from bat guano. Next‐generation sequencing was used to collect data on bat species composition, individual genotypes, sex ratios, diet, parasites, and the presence of White‐nose syndrome.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…Carroll et al (2018) target the interface between MIS methods and NGS approaches. Minimally invasive samples are often opportunistically collected from the environment and consequently contain limited amounts of DNA, which can restrict the subsequent molecular analyses of these samples, especially when applying NGS methods.The authors provide guidance on how to transition legacy datasets of microsatellites or mitochondrial DNA to genomic platforms and integrate novel methods such as microbiome and epigenetic studies Swift et al (2018). utilized MIS methods and multifaceted DNA metabarcoding (MDM) to obtain six different data classes of genetic information from bat guano.…”
mentioning
confidence: 99%